Caffeine consumption during early pregnancy impairs oviductal embryo transport, embryonic development and uterine receptivity in mice() - Qian, Jingjing (Biol Reprod, 2018)
Caffeine consumption has been widely used as a central nervous system stimulant. Epidemiological studies, however, have suggested that maternal caffeine exposure during pregnancy is associated with increased abnormalities, including decreased fertility, delayed conception, early spontaneous abortions, and low birth weight. The mechanisms underlying the negative outcomes of caffeine consumption, particularly during early pregnancy, remain unclear. In present study, we found that pregnant mice treated with moderate (5 mg/kg) or high (30 mg/kg) dosage of caffeine (intraperitoneally or orally) during preimplantation resulted in retention of early embryos in the oviduct, defective embryonic development, and impaired embryo implantation. Transferring normal blastocysts into the uteri of caffeine-treated pseudopregnant females also showed abnormal embryo implantation, thus indicating impaired uterine receptivity by caffeine administration. The remaining embryos that managed to implant after caffeine treatment also showed increased embryo resorption rate and abnormal development at mid-term stage, and decreased weight at birth. In addition to a dose-dependent effect, significant variations between individual mice under the same caffeine dosage were also observed, suggesting different sensitivities to caffeine, similar to that observed in human populations. Collectively, our data revealed that caffeine exposure during early pregnancy impaired oviductal embryo transport, embryonic development, and uterine receptivity, which are responsible for abnormal implantation and pregnancy loss. The study raises the concern of caffeine consumption during early stages of pregnancy.